Is C-reactive protein elevated in obstructive sleep apnea? a systematic review and meta-analysis. (4th July 2019) - Van der Touw, Tom; Andronicos, Nicholas Matthew; Smart, Neil
Abstract: Purpose: This study examined whether circulating C-reactive protein (CRP) is elevated in obstructive sleep apnoea (OSA) independent of the confounding effects of comorbidities, smoking, body mass index (BMI), age and gender. Methods: A systematic review of the literature was performed using PubMed, Embase and Cochrane databases from 1 January 1997 to 1 November 2017 using the key words obstructive sleep apnoea and C-Reactive protein to identify full text English language studies that compared CRP in adult non-smoking OSA participants without comorbidities and adult healthy non-smoking control participants matched for BMI, age and gender. Data from eligible studies were subjected to meta-analysis using RevMan version 5.3. Results: Five studies (219 OSA participants, 116 controls) met the selection criteria. The total standard mean difference for circulating high sensitivity CRP was 0.61 mg/dL higher in OSA participants than in control participants (confidence interval: 0.38 to 0.84, p < 0.00001), with low between-studies heterogeneity (df = 7, p = 0.16, I 2 = 33%) and minimal evidence of publication bias. Conclusions : CRP levels in non-smoking OSA participants without comorbidities were increased relative to levels in healthy matched non-smoking control participants, suggesting that pharyngeal or systemic inflammatory effects attributable to OSA may elevate CRP.